Compartmental resection of peripheral nerve tumours with limb preservation in 16 dogs (1995–2011). (August 2017) - van Stee, L.; Boston, S.; Teske, E.; Meij, B.
Highlights: Local resection of canine peripheral nerve tumours led to good functional outcome of the affected limb. Post-surgical limb use and lameness scores improved in most cases. Complete margins were achieved in 5/9 cases with spinal canal involvement. Complete margins were associated with prolonged survival. Abstract: Peripheral nerve tumours (PNTs) affecting the limbs may lead to chronic pain, lameness and/or monoparesis that is refractory to medical treatment. The most common radical therapy for PNTs has been surgical excision with limb amputation. However, compartmental resection with preservation of the limb has been performed by the authors with favourable clinical results and therefore this bi-institutional retrospective study was undertaken to assess limb function, survival and recurrence. Sixteen dogs that had been diagnosed with PNTs between 1995 and 2011 met the inclusion criteria for this study. In the majority of the cases, good to excellent limb function was achieved. The overall median survival time (MST) was 1303 days (42.8 months; range, 14 days–4639 days, [0.5–152.4 months]), with two dogs still alive at time of evaluation. Non-infiltrated margins were the best prognostic indicator; dogs with non-infiltrated margins had a MST of 2227 days ( P  < 0.001) compared to dogs with infiltrated margins (MST of 487 days). The 1-year calculated survival rate was 68.8% and the 2- and 3-year calculated survival rates were 62.5%. Surgical treatment with tumour removal and limb spare for proximal and distal PNTs can be successful. Compartmental excision can lead to good limb function, producing survival comparable to limb amputation, and should therefore be considered as an alternative to limb amputation in canine PNTs.